Developing Hierarchical Schemas and Building Schema Chains Through Practice Play Behavior - Kumar, Suresh; Shaw, Patricia; Giagkos, Alexandros; Braud, Raphäel; Lee, Mark; Shen, Qiang (Frontiers in Neurorobotics, 2018)
Examining the different stages of learning through play in humans during early life has been a topic of interest for various scholars. Play evolves from practice to symbolic and then later to play with rules. During practice play, infants go through a process of developing knowledge while they interact with the surrounding objects, facilitating the creation of new knowledge about objects and object related behaviours. Such knowledge is used to form schemas in which the manifestation of sensorimotor experiences is captured. Through subsequent play, certain schemas are further combined to generate chains able to achieve behaviours that require multiple steps. The chains of schemas demonstrate the formation of higher level actions in a hierarchical structure. In this work we present a schema-based play generator for artificial agents, termed Dev-PSchema. With the help of experiments in a simulated environment and with the iCub robot, we demonstrate the ability of our system to create schemas of sensorimotor experiences from playful interaction with the environment. We show the creation of schema chains consisting of a sequence of actions that allow an agent to autonomously perform complex tasks. In addition to demonstrating the ability to learn through playful behaviour, we demonstrate the capability of Dev-PSchema to simulate different infants with different preferences towards novel vs. familiar objects.